KAMPUNG DEVELOPMENT TOWARD SMART CITY - Tanti Satriana R. Nasution; Purwanita Setijanti; Asri Dinapradipta; Angger Sukma Mahendra; Susetyo Firmaningtyas; Muhammad Ainul Yaqin (Journal of Architecture&ENVIRONMENT, 2018)
The city of Surabaya that formed from maritime activities to lead to trade and industrial activities will form settlements in the form of kampung. Kampung became an important part in the development of a city because this area became a place to grow and move most of the middle class population and below. However, the rapid development of the city of Surabaya towards the modern has resulted in the existence of the kampung in Surabaya increasingly recessive. Long-lived kampung like Kampung Kaliasin, pressed by the development of urban and socio-economic mobility, are experiencing worsening kampung conditions. The pressure from the surrounding environment is great. Not only social and economic issues, but also environmental issues (climate, sanitation, a forestation, etc.) are salient. The Surabaya City Government is attempting to address the problem through the concept of Smart City Surabaya. The question to be addressed here is how the development of the urban kampung, for example Kampung Kaliasin, is to proceed in the direction of Smart City Surabaya. The method used is descriptive and qualitative. The variables to be studied are aspects of smart city covering Smart Government, Smart Economy, Smart Life, Smart Living, Smart People, and Smart Mobility. These are analyzed in relation to the readiness of the city to develop toward Smart City Surabaya.